P19 | LOQANT: IMAGEJ SCRIPT FOR ANALYSING NUCLEO-CYTOPLASMIC PROTEIN TRANSLOCATION (European Journal of Histochemistry)
Nucleocytoplasmic shuttling is a key regulatory mechanism in cellular signalling. Many proteins, including nuclear receptors, transit between the cytoplasm and the nucleus in order to control gene expression and other vital processes. Monitoring their subcellular localisation using immunostaining provides valuable insights into cellular responses, disease mechanisms and therapeutic strategies. However, manual assessment is very time consuming, introduces a considerable degree of subjectivity and bias, and is unsuitable for high-throughput analysis. Despite its importance, there is currently a lack of standardised, user-friendly tools that can quantitatively assess nucleocytoplasmic translocation efficiently and reproducibly. To evaluate the variability of manual scoring when assessing nuclear receptor translocation, 20 micrographs of SH-SY5Y cells immunostained for PPARα were analysed independently by six observers with varying levels of expertise. As expected, manual grading showed considerable variability and poor interobserver reliability, as determined by intraclass correlation coefficient analysis. As a solution, we developed LoQANT (Localisation and Quantification of Antigen Nuclear Translocation), an open-source, Python-based ImageJ/Fiji script. It reliably and efficiently quantifies nucleocytoplasmic shuttling in both DAB- and fluorescence-stained specimens. This single-cell-based approach specifically assesses the presence and intensity of the nuclear signal, independently of cytoplasmic staining, thus avoiding confounding background interference. Depending on the detection method, it can perform both semiquantitative and quantitative analyses.